THE EFFECT OF WORK ETHICS AND LEARNING AGILITY ON EMPLOYEE PERFORMANCE THROUGH KNOWLEDGE UTILIZATION, WITH ORGANIZATIONAL COMMITMENT AS A MODERATING VARIABLE AT PT MIDTOU ARYACOM FUTURES IN BANDAR LAMPUNG - Putri Rahmadani; Febrianty; Muhammad Irfan Pratama (International Journal of Multidisciplinary Reseach, 2026)
Employee performance through Knowledge Utilization with Organizational Commitment as a moderating variable at PT Midtou Aryacom Futures in Bandar Lampung. Work Ethics represents the values of discipline, responsibility, and integrity within a high-risk financial services environment, while Learning Agility reflects employees' ability to quickly learn and adapt to market changes. Knowledge Utilization plays a role in leveraging knowledge for decision-making and work innovation, which is expected to mediate the relationship between Work Ethics and Learning Agility with employee performance. This research employs a quantitative approach using a structural equation modeling method based on Partial Least Squares (PLS-SEM). The findings are expected to provide empirical contributions to human resource management, particularly in enhancing employee performance effectiveness through the development of work ethics, learning agility, and optimal knowledge utilization, as well as strengthening organizational commitment, which functions as a moderating variable. Practical implications for PT Midtou Aryacom Futures include the development of training programs and human resource management that can support sustainable organizational success.